KUALITAS PELAYANAN PASPOR DI KANTOR IMIGRASI KELAS 1 KOTA SURAKARTA - Aris Tri Haryanto, Sri Riris Sugiyarti, Dewi Alâan Shary, (Solidaritas, 2018)
Abstract This research was conducted with the aim of describing the quality of Service Passports at the Immigration Office grade 1. This research is a descriptive qualitative research that describe the State of the real in the Immigration Office grade 1 passport services in Surakarta. Quality of service is the level of conformity of desire or the demands of customers by implementing a more responsive service to achieve customer satisfaction. Data collection techniques used in this research, i.e., interview, observation and documentation. The informant is determined using a purposive sampling technique by choosing which is considered research problem in knowing, the selected informer is the Kasubsi Insarkom of the immigration and Passport service users at the Immigration Office grade 1 Surakarta is Tri Widodo, Ferry and Tiara. Data analysis techniques using interactive model. The results of this research, service passport at the Immigration Office grade 1 Surakarta already qualified. Passport services based on quality assessment indicators that have been used, namely the first tangibles (direct evidence) as seen from the existence of the facility as well as the supporting infrastructure is already good. Reliability (reliability) reliability employees already well because employees have gotten training-previous training in order to provide a maximum service. Responsiveness (responsiveness) seen from the dexterity in delivering appropriate services officer in the SOP and has the motto of the Ministry is PASTI (Professional, accountable, synergy, transparent, innovative). Assurance (assurance) gives employees the ability to foster a sense of trust towards the services provided by trying to improve the quality of service through the spread of kuisoner. Empaty is a form of caring employees in facilitating the service of the complaint via email and twitter.Keywords: quality of, public services.